Influence of Reward Strategies on Employee Performance in Public University Campuses in Kericho County, Kenya - Cheruiyot, Benjamin Bett; Kalei, Anne (Human Resource Management Academic Research Society, 2020)
The focus of this study was to investigate the influence of reward strategies on employee performance in public university campuses in Kericho County, Kenya. The study was motivated by concerns on employee performance in public university campuses despite the various reward strategies adopted by the public institutions to enhance employee performance. The study adopted a cross-sectional survey design. A sample of 106 employees, representing 26% of the target population, was selected from four public university campuses namely; University of Kabianga (UK), Moi University (MU), Kenyatta University (KU), and Kisii University (KSU). Stratified random sampling was utilized in selecting the respondents for the study. Data was collected through questionnaire and analyzed using both descriptive and inferential statistics. A pilot study was conducted on data collection instrument to pre-test its validity before the main survey, while data reliability was measured using Cronbach’s alpha coefficient. Statistical Package for Social Sciences (SPSS) version 23.0 was used to aid in coding, entry and analysis of quantitative data. Finally, there is conclusion and recommendation based on the findings. The study found out that the relationship between reward strategy and employee performance was significantly positive. The conclusion from the findings of this study is that motivated employees are the main drivers of the public institutes’ performance. In view of the findings, the study recommends that public universities improve reward strategies in order to improve the level of employee performance.
Keywords: Employee; Performance; Reward; Strategy.